Compatibilidades entre o psicodrama de Moreno e a Daseinsanalyse de Boss na prática psicoterapêutica - Calderoni, Carla Regina (2010)
This study aimed at identifying compatibilities between Jacob Levy Moreno s psychodrama and Medard Boss s Daseinsanalysis in psychotherapeutic practice. Both approaches rose from the same historical context, with common origins in the vein of philosophical existential phenomenology. Moreno s professional trajectory was presented, referencing his four creative moments and the concepts and psychotherapeutic practices that arose in each of these moments. Daseinsanalysis s founding principles and its method of psychotherapeutic treatment, which was proposed by Boss drawing from Heideggerian ontology, are reviewed. Fundamental similarities in their psychotherapeutic practice were found in Moreno s Psychodrama and Boss s Daseinsanalysis, which are then shown through examples of Moreno s and Boss conduction of clinical cases. The compatibilities were verified in both authors practices. Without damaging psychodramatic methodology, Moreno acts as a daseinsanalyst when welcomes patients as they are, offering the possibility to understand and transform their being-in-the-world. In the same way, maintaining loyalty to the daseinanalytical method, Boss acts as a psycho dramatist when he enables his patient to experience his childlike state in a spontaneously creative way, offering a shelter for her to re-live principal moments of his childhood. From those identified compatibilities, it is contended that psychotherapists and adherents to psychotherapy can benefit from the integration of the two approaches, since they coexist without opposition. A psychodramatist can, thanks to his psychotherapeutic practices, exercise Bossian Daseinanalysis and daseinanalysts can, in their psychotherapeutic practices, exercise Morenian psychodrama